2014
DOI: 10.1016/j.jbiomech.2014.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics endpoints for assessment of adenotonsillectomy outcome in obese children with obstructive sleep apnea syndrome

Abstract: Background Improvements in obstructive sleep apnea syndrome (OSAS) severity may be associated with improved pharyngeal fluid mechanics following adenotonsillectomy (AT). The study objective is to use image-based computational fluid dynamics (CFD) to model changes in pharyngeal pressures after AT, in obese children with OSAS and adenotonsillar hypertrophy. Methods Three-dimensional models of the upper airway from nares to trachea, before and after AT, were derived from magnetic resonance images obtained durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…Analysis of the motion of the jaw, tongue, pharyngeal walls, soft palate, and epiglottis revealed how each region of anatomy influences the volume of the airspace and the cross‐sectional area of the upper airway along its length. Many studies have previously shown the relationship between airway cross‐sectional area and airway resistance, with narrower sections increasing the subject's work of breathing. Therefore, mapping the dynamic behavior of the upper airway cross‐section throughout a breath is vital to accurately predicting the airway pressure losses in computational and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the motion of the jaw, tongue, pharyngeal walls, soft palate, and epiglottis revealed how each region of anatomy influences the volume of the airspace and the cross‐sectional area of the upper airway along its length. Many studies have previously shown the relationship between airway cross‐sectional area and airway resistance, with narrower sections increasing the subject's work of breathing. Therefore, mapping the dynamic behavior of the upper airway cross‐section throughout a breath is vital to accurately predicting the airway pressure losses in computational and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…A range of 0.5oy þ o3 was also reported by Dehbi (2011). For realistic complex geometries like the present CT-scan based lung model geometry, a tetrahedral mesh style has been considered appropriate in many past studies (Alzahrany and Banerjee, 2015;Choi et al, 2010;Farkas and Balashazy, 2007;Gemci et al, 2008;Luo et al, 2014). The mesh sensitivity was examined and it was found that a mesh of size 2.42 Â 10 6 elements resolves 491% of turbulence kinetic energy for all considered HFOV frequency and is considered appropriate as it resolves 480% of the total energy (Pope, 2001).…”
Section: Numerical Methods and Experimental Validationmentioning
confidence: 63%
“…This method can give additional functional information about the upper airway. A limited number of studies have applied FRI in paediatric OSA and mainly consisted of case reports or investigated whether FRI could provide more insight in the pathophysiology of OSA . Furthermore, these studies only included a small number of patients and mainly studied children with underlying conditions including obesity .…”
Section: Introductionmentioning
confidence: 99%